Free standing dual phase cathode tapes – scalable fabrication and microstructure optimization of garnet-based ceramic cathodes. Issue 5 (26th November 2021) - Rosen, Melanie; Finsterbusch, Martin; Guillon, Olivier; Fattakhova-Rohlfing, Dina
Abstract : Free-standing garnet based ceramic cathodes with tailored microstructure enable dramatically increased full-cell capacity. Abstract : To make ceramic based all-solid-state batteries competitive for the battery market, a shift from the separator supported cell-design for lab cells to a scalable, cathode-supported one is necessary to improve the energy density. Using tape casting, we were able to demonstrate for the first time all-ceramic free-standing LiCoO2 (LCO)/Li6.45 Al0.05 La3 Zr1.6 Ta0.4 O12 (LLZO) mixed cathodes with high capacities and active material utilization. Further morphology engineering by introduction of a sequential layer casting enabled us to tailor the microstructure of the mixed cathodes resulting in opposite concentration gradients for the active material and the electrolyte over the thickness of the cathode. With this optimized microstructure, we were able to increase the discharge capacity of the free-standing mixed cathodes to 2.8 mA h cm −2 utilizing 99% of the theoretical capacity. For the oxide garnet-based system, both the scalable fabrication method and the achieved electrochemical performance demonstrates industrial relevance for the first time. Additionally, the obtained free-standing cathodes have sufficient mechanical stability to allow the application of hybrid and ultra-thin separators to further increase the energy density on the full cell level.